Pragmatic Failure of Students Conversation in Speaking Class of Xi Grade in Ma Al-Hikmah Tanon - Indah Musfirotul Fitria; Wuri Rahmawati (Surakarta English and Literature Journal, 2020)
speaker and hearer, but the conversation can be continued. Accordingly, the pragmatic role is needed. Nevertheless, many cases used pragmatically might fail for many reasons, such as: cross-culture understanding, even misunderstanding of grammatical form. That case happens not only in real life conversation, but also in the classroom. This article is aimed to analyze the pragmatics failures of English students’ conversation in the speaking class. The discussion starts from the definition of Pragmatic and Speech act, and Pragmatic Failures in speaking class. It will be followed by the analysis of some conversations of the pragmatic failure in speaking class of EFL. This study shows that there are ten conversations of pragmatic failure. Based on those conversations, the researcher found the cases, firstly, there are kinds of speech act in English students’ conversation in the speaking class, namely: directive, assertive, declaration depended on Levinson's theory. Moreover, secondly, pragmatic failure happens in English students’ conversation in speaking class is pragmalinguistics failure.